The Effects of Sales Reports Business Intelligence on Employee Performance - Aini, Qurotul; Harahap, Eka Purnama; Faradilla, Fitri (APTISI Transactions on Management (ATM), 2020)
Abstract Selling and buying activities have been done often since long ago, and this study will be discussed about the use of technological advances, especially in the field of financial management by utilizing e-commerce. When carrying out financial data collection, staff can make recapitulation by writing each transaction in the ledger, then counting the data to be the income information. However, the process is not in tune with current technological progress, because it still use a data collection process that requires a lot of time and energy. Thus, to overcome this problem, e-commerce websites are used so that it can manage finances accurately and quickly. In this study, there are 4 (four) problems that will be overcome with 2 (two) methods, and 1 (one) solution as the answer. The advantages of e-commerce website is that it has an informative viewboard regarding financial management, which can be accessed anytime and anywhere, so it is concluded that the use of e-commerce website is able to overcome the problems found in the financial management field of Raharja Internet Cafe at Perguruan Tinggi Raharja.